Juvenile Justice: Genesis and Current State in Ukraine - Kyrylenko, Mariia (Journal of Legal Studies, 2020)
In this paper, the problem of the functioning of the juvenile justice as a system of all parts of the state mechanism, that deal with the problems of protection and socializing of children is considered. It is determined that the protection of children's rights in Ukraine is an urgent question. That is why providing proper conditions for life, development and socialization of the younger generation has become one of the priorities for the state policy of Ukraine. Hence, juvenile justice is one of the most effective ways to protect the rights and interests of children and youth. However the tendencies of formation of the juvenile legal policy of the state influence whether legal regulation of children’s protection can be implemented in the legal system of the state to that extent that it promotes the development of children's protection. Thus, there is a necessity to analyze the genesis, development and the current state of the juvenile law in Ukraine taking into account the practice of foreign states and defining the further perspectives of the juvenile law.